Time-efficient A* Algorithm for Robot Path Planning. (2016) - Guruji, Akshay Kumar; Agarwal, Himansh; Parsediya, D.K.
Abstract: The current era is mainly focused on the modernization, industrialization, automation and development. For which, the human task are replaced by robots to achieve good accuracy, high efficiency, speed and multiplicity. In industries, these robots are employed to carry heavy objects in working place. As the environment or working area may be dynamically changing, the algorithm or the rules must be devised to ensure an optimistic collision-free path. A* algorithm is a heuristic function based algorithm for proper path planning. It calculates heuristic function's value at each node on the work area and involves the checking of too many adjacent nodes for finding the optimal solution with zero probability of collision. Hence, it takes much processing time and decreases the work speed. The modifications in A* algorithm for reducing the processing time are proposed in this paper. The proposed A* algorithm determines the heuristic function's value just before the collision phase rather than initially and exhibits a good decrement in processing time with higher speed. This paper involves MATLAB simulation of robot movement from source to goal. Several cases are considered with proposed A* algorithm which exhibit maximum 95% reduction in processing time.